(untitled) (Heródoto: Revista do Grupo de Estudos e Pesquisas sobre a Antiguidade Clássica e suas Conexões Afro-asiáticas, 2016)
The article begins with a description of iconography as historical document. Image in Antiquity had a specific function: to present to a particular social group, mostly illiterate, something that represented the edge of power. It not only legitimized an emperor or king, but was also a type of advertising.